Computer communications and networks - Freer, John R (IEEE Press, 1996)
This essential text book is a constant reference companion for students and practitioners in need of an accessible technical introduction to the field. Thoroughly revised and updated, this new edition is complete with the most recent developments in standards and architectures, including ATM, B-ISDN, SNMP, TCP/IP, and other state-of-the-art features emerging in the computer communications field.